LOCAL WISDOM: A SOLUTIONTO SURPASSHEDONISMEFFECTS ONENVIRONMENTPOLLUTION - Armaidy Armawi (Faculty of Geography, Universitas Gadjah Mada, 2010)
Science and technology on modern human create dualism result whichcomplete opposite. Those results are as proper instrument to fulfill increasinglycomplex of human needand as nature exploltatlon instrument with dehumanizationas result and also the trap of historical ratlona/lty. The hedonism ethics trend has asignificant role on the second result. It means, whether the hedonism terminologyis /lmlted with